2006
DOI: 10.1158/1078-0432.ccr-05-1732
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Activated AKT Expression in Soft-Tissue Sarcoma

Abstract: Purpose: AKT is a serine/threonine kinase which is important in tumorigenesis. Several molecules involved in AKT pathway are dysregulated in various kinds of human cancers. Patients and Methods: Ninety-three patients (53 males and 40 females), ages ranging from 19 to 77 years (median, 57 years), with localized soft-tissue sarcomas arising in the trunk and extremities, were analyzed. Immunoperoxidase procedure (avidin-biotin complex method) was done on paraffin-embedded sections with anti^phosphorylated AKT (Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 36 publications
2
50
1
Order By: Relevance
“…Although FOXO1A is generally regarded as a direct substrate of AKT1, 16 it remains controversial 26 and soft tissue sarcoma, 27 while no association was observed in prostate cancer 15 and in breast cancer. 13 The present study showed a positive correlation between the expression of pFOXO1A and that of pAKT1 (Po0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Although FOXO1A is generally regarded as a direct substrate of AKT1, 16 it remains controversial 26 and soft tissue sarcoma, 27 while no association was observed in prostate cancer 15 and in breast cancer. 13 The present study showed a positive correlation between the expression of pFOXO1A and that of pAKT1 (Po0.001).…”
Section: Discussionmentioning
confidence: 99%
“…3,5 However, the expression profiles of the molecules along the Akt/mTOR pathway have been analyzed in a relatively small number of clinical materials. 5,13,14 Some authors investigated Akt/mTOR pathway involvement in STS series and demonstrated a correlation between Akt activation and a worse prognosis 15 or a greater probability of metastasis 13 ; whereas, to our knowledge, no investigations have focused on SS as a single entity, and the prognostic impact of this pathway on SS has remained to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that constitutive activation of Akt, through PI3K amplification or PTEN mutation, contributes to the oncogenic process and is associated with a poor prognosis and resistance to chemo-and radio-therapy (94). Indeed, Akt activation is one of the most frequent molecular alterations in cancers, including melanoma, gastric, pancreatic, breast, sarcoma and prostate cancer (95)(96)(97)(98). While there are instances where the three Akt isoforms are able to compensate for each other, recent research show that their tissue expression patterns and functions are different (99,100).…”
Section: Phosphatidylinositol 3-kinase/protein Kinase B (Pi3k/akt) Simentioning
confidence: 99%